ADSORPSI ZAT WARNA METHYLENE BLUE MENGGUNAKAN ADSORBEN KOMPOSIT Fe3O4-ARANG AKTIF KULIT LAI [Durio Kutejensis (Hassk.)Becc.] - Rahmawati, Rahmawati; Wirawan, Teguh; Koesnarpadi, Soerja (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Methylene blue is a synthetic dye commonly used in industry. Methylene blue is not very toxic to humans, but can cause skin irritation, eye irritation, and systemic effects including blood changes. This research aims to utilize lai bark activated charcoal composited with Fe3O4 as an adsorbent to adsorb methylene blue dye. Fe3O4-lai skin activated charcoal composite adsorbent was synthesized using the co-precipitation method from FeSO4.7H2O and FeCl3.6H2O then combined with lai skin activated charcoal. The Fe3O4-activated charcoal composite for skin was characterized using FTIR. The results of composite characterization using FTIR show that there is a wave number of 596.00 cm-1 which is the Fe-O group. The research results showed that the optimum conditions for the adsorption of methylene blue dye by the Fe3O4-activated charcoal composite adsorbent for lai skin were 60 minutes, pH 8, concentration 250 mg/L and following the Langmuir isotherm. The maximum adsorption capacity of Fe3O4-lai skin activated charcoal composite was 197.8792 mg/g. Keywords: Adsorption, Methylene Blue Dye, Composite, Lai Leather